2020
DOI: 10.1021/acs.jcim.0c00081
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices in Utilization of 2D-NMR Spectral Data as the Input for Chemometric Analysis in Biopharmaceutical Applications

Abstract: Quality attributes (QAs) are measureable parameters of a biologic that impact product safety and efficacy and are essential characteristics that are linked to positive patient health outcomes. One QA, higher order structure (HOS), is directly coupled to the function of protein biologics, and deviations in this QA may cause adverse effects. To address the critical need for HOS assessment, methods for analyzing structural fingerprints from 2D nuclear magnetic resonance spectroscopy (2D-NMR) spectra have been est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…As such, the PCA on peak position confirms the reproducibility of the measurement and shows the applicability of the method even at 500 MHz. Validation of a cluster assignment for a spectrum could be evaluated using the Dunn index or silhouette values ( Brinson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the PCA on peak position confirms the reproducibility of the measurement and shows the applicability of the method even at 500 MHz. Validation of a cluster assignment for a spectrum could be evaluated using the Dunn index or silhouette values ( Brinson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…To fully harmonize the experimental methods and the analysis components of the 2D-NMR method, a global interlaboratory study was conducted with equal representation from academia, government, and industry, involving 26 laboratories from 9 countries, using the NIST-Fab, the Fab fragment derived from papain cleavage of the NISTmAb as the model therapeutic protein for the IgG1 molecular class ( Brinson et al, 2019 ). In addition, two subsequent studies ( Brinson et al, 2020 ; Sheen et al, 2020 ) followed, which used the interlaboratory data to further develop NMR processing and analysis tools well suited for biopharmaceutical applications.…”
Section: Nuclear Magnetic Resonance Higher Order Structure Interlabor...mentioning
confidence: 99%
“… 51 This technique can also be used to evaluate the behavior of one molecule that is subjected to different solution or instrument conditions. 38 , 40 One criterion for PCA is that the input data array, across all samples, must have an equivalent number of values. Therefore, the direct application of PCA to 2D NMR, of different Ab(L/F)s, is not straightforward because the structural scaffolds, size and behavior of samples will generate a different number of resonance peaks within each spectrum.…”
Section: Resultsmentioning
confidence: 99%
“… 31 , 36 , 37 Natural abundance 2D NMR applied to mAbs and Fabs has largely been championed by the Marino group, where they demonstrated multiple applications including detected differences in mAb glycosylation, reported a statistical approach to assess large NMR signal differences between a set of biologics samples, and established the robustness and variability of 2D [ 1 H, 13 C]-HSQC fingerprinting for biosimilar comparison. 30 , 36 , 38–41 However, extracting and comparing quantitative aspects between different types of Ab(L/F)s still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that Fc and Fab fragments yielded methyl fingerprint spectra in a much shorter time in approximately 30 min [52]. It should be noted that an international effort of standardization to make the 2D NMR method a highly confident routine way to assess HOS of mAb is underway [63][64][65][66].…”
Section: Obtaining Structural Fingerprint By 1 H-detected Multidimensional Nmrmentioning
confidence: 99%